Pathogen-specific burdens of community diarrhoea in developing countries: a multisite birth cohort study (MAL-ED) - James A Platts-Mills, MD; Sudhir Babji, MD; Ladaporn Bodhidatta, MD; Jean Gratz, BSc; Rashidul Haque, MD; Alexandre Havt, PhD; Benjamin JJ McCormick, DPhil; Monica McGrath, ScD; Maribel Paredes Olortegui, BSc; Amidou Samie, PhD; Sadia Shakoor, MBBS; Dinesh Mondal, MD; et al. (Elsevier, 2015)
Background: Most studies of the causes of diarrhoea in low-income and middle-income countries have looked at severe disease in people presenting for care, and there are few estimates of pathogen-specific diarrhoea burdens in the community. Methods: We undertook a birth cohort study with not only intensive community surveillance for diarrhoea but also routine collection of non-diarrhoeal stools from eight sites in South America, Africa, and Asia. We enrolled children within 17 days of birth, and diarrhoeal episodes (defined as maternal report of three or more loose stools in 24 h, or one loose stool with visible blood) were identified through twice-weekly home visits by fieldworkers over a follow-up period of 24 months. Non-diarrhoeal stool specimens were also collected for surveillance for months 1-12, 15, 18, 21, and 24. Stools were analysed for a broad range of enteropathogens using culture, enzyme immunoassay, and PCR. We used the adjusted attributable fraction (AF) to estimate pathogen-specific burdens of diarrhoea. Findings: Between November 26, 2009, and February 25, 2014, we tested 7318 diarrhoeal and 24 310 non-diarrhoeal stools collected from 2145 children aged 0-24 months. Pathogen detection was common in non-diarrhoeal stools but was higher with diarrhoea. Norovirus GII (AF 5·2%, 95% CI 3·0-7·1), rotavirus (4·8%, 4·5-5·0), Campylobacter spp (3·5%, 0·4-6·3), astrovirus (2·7%, 2·2-3·1), and Cryptosporidium spp (2·0%, 1·3-2·6) exhibited the highest attributable burdens of diarrhoea in the first year of life. The major pathogens associated with diarrhoea in the second year of life were Campylobacter spp (7·9%, 3·1-12·1), norovirus GII (5·4%, 2·1-7·8), rotavirus (4·9%, 4·4-5·2), astrovirus (4·2%, 3·5-4·7), and Shigella spp (4·0%, 3·6-4·3). Rotavirus had the highest AF for sites without rotavirus vaccination and the fifth highest AF for sites with the vaccination. There was substantial variation in pathogens according to geography, diarrhoea severity, and season. Bloody diarrhoea was primarily associated with Campylobacter spp and Shigella spp, fever and vomiting with rotavirus, and vomiting with norovirus GII. Interpretation: There was substantial heterogeneity in pathogen-specific burdens of diarrhoea, with important determinants including age, geography, season, rotavirus vaccine usage, and symptoms. These findings suggest that although single-pathogen strategies have an important role in the reduction of the burden of severe diarrhoeal disease, the effect of such interventions on total diarrhoeal incidence at the community level might be limited. Funding: Bill & Melinda Gates Foundation.